Immunomodulation of periodontitis with SPMs - Sahni, Vaibhav; Van Dyke, Thomas E. (Frontiers in Oral Health, 2023)
Inflammation is a critical component in the pathophysiology of numerous disease processes, with most therapeutic modalities focusing on its inhibition in order to achieve treatment outcomes. The resolution of inflammation is a separate, distinct pathway that entails the reversal of the inflammatory process to a state of homoeostasis rather than selective inhibition of specific components of the inflammatory cascade. The discovery of specialized pro-resolving mediators (SPMs) resulted in a paradigm shift in our understanding of disease etiopathology. Periodontal disease, traditionally considered as one of microbial etiology, is now understood to be an inflammation-driven process associated with dysbiosis of the oral microbiome that may be modulated with SPMs to achieve therapeutic benefit.